Perlindungan Hukum Debitur dalam Perjanjian Pinjaman Online dan Efektivitas Mekanisme Penagihan - Hamzah Rizky Fadhillah Saragih; Suhaila Zulkifli; Tajuddin Noor (CV WAHANA PUBLIKASI, 2026)
This study aims to identify legal gaps in Indonesia’s regulatory framework for debtor protection in online lending services, evaluate the effectiveness of debt collection mechanisms implemented by fintech lending providers, and formulate legal solutions to strengthen protection against abusive collection practices. This research employs a normative legal method with a qualitative approach by examining statutory regulations, legal doctrines, and relevant literature, particularly the Financial Services Authority Regulation (POJK) Number 10/POJK.05/2022, the Consumer Protection Law, and Law Number 27 of 2022 on Personal Data Protection. The findings reveal that Indonesia has established preventive protection through transparency and consumer information disclosure, as well as repressive protection through complaint and dispute resolution mechanisms, including the Financial Services Authority Consumer Protection Application (APPK) and the Financial Services Sector Alternative Dispute Resolution Institution (LAPS SJK). However, implementation remains ineffective due to legal gaps, including the absence of detailed technical standards for ethical debt collection, weak supervision of third-party debt collectors, inadequate victim recovery mechanisms, and administrative sanctions with limited deterrent effects. Violations such as intimidation, unauthorized disclosure of personal data, harassment of emergency contacts, and the use of false legal documents persist. Comparative analysis with Singapore, the United States, and the European Union indicates that Indonesia primarily requires stronger implementation and enforcement rather than additional legislation. Accordingly, this study recommends regulatory harmonization, stronger supervision, standardized debt collection guidelines, and improved legal and digital literacy to strengthen sustainable debtor protection.